Development of Braking Force Distribution Strategy for Dual-Motor-Drive Electric Vehicle - Binbin Sun; Pengwei Wang; Song Gao; Jie Yu; Zhangu Wang (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
In the development of the optimal braking force distribution strategy for a dual-motor-drive electric vehicle (DMDEV) with a series cooperative braking system, three key factors were taken into consideration, i.e. the regenerative force distribution coefficient between the front and the rear motor (Î²), the energy recovery coefficient at the wheels (Î±3), and the front-and-rear-axle braking force distribution coefficient (Î»). First, the overall power loss model of the two surface-mounted permanent magnetic synchronous motors (SMPMSMs) was created based on the d-q axis equivalent circuit model. The optimal relationship of Î² and the overall efficiency of the dual-motor system were confirmed, where the latter was quite different from that obtained from the traditional look-up table method for the motors' efficiency. Then, four dimensionless evaluation coefficients were used to evaluate braking stability, regenerative energy transfer efficiency, and energy recovery at the wheels. Finally, based on several typical braking operations, the comprehensive effects of the four coefficients on braking stability and energy recovery were revealed. An optimal braking force distribution strategy balancing braking stability and energy recovery is suggested for a DMDEV with a series cooperative braking system.